FFMI: A Pivotal Indicator Bridging Pulmonary, Sleep, and Systemic Factors in COPD–OSA Overlap Patients - Wang, Liang; Shen, Ying-Ying; Qian, Rui-Qi; Zhang, Xiu-Qin; Shen, Xu-Rui; Chen, Cheng (International journal of chronic obstructive pulmonary disease, 2025)
Overlap Syndrome (OVS), combining Chronic Obstructive Pulmonary Disease (COPD) and Obstructive Sleep Apnea (OSA), is common yet often unrecognized. This study aims to compare the Fat - Free Mass Index (FFMI) between OVS and simple COPD patients and analyze subgroup differences in OVS for better early identification and severity assessment. Clinical data of 364 patients (203 in COPD group, 161 in OVS group) were analyzed regarding clinical features, pulmonary function, sleep apnea, etc. The OVS group was divided into low-FFMI and normal-FFMI subgroups (the cutoff value of FFMI < 17kg/m²) for correlation analysis. Statistically significant differences in frequency of acute exacerbations and hospitalizations in the past year, and comorbidities were observed between the COPD group and OVS group (all p < 0.05). The OVS group exhibited significantly lower FEV %pred, FEV /FVC, 6MWT, FFMI, and L-SaO compared to the COPD group (all p < 0.05), while AHI, ESS, CAT, and MMRC were higher. Patients with lower FFMI demonstrated lower FEV %pred, FEV /FVC, L-SaO2, and 6MWT than those with normal FFMI. Additionally, AHI, MMRC, frequency of acute exacerbations, and hospitalizations in the past year were higher (all p < 0.05) in this group. Correlation analysis revealed that in the OVS group, FFMI positively correlated with FEV1%pred and FEV1/FVC, and negatively with AHI, MMRC, exacerbation/hospitalization frequency. OVS patients had distinct features like more exacerbations, and lower lung function. The OVS subgroup with different FFMI showed significant differences in lung function and sleep indices. FFMI is closely related to pulmonary function, sleep disorder indices, and exacerbation frequency, suggesting its potential as an important indicator for early OVS identification and severity evaluation despite no significant difference in BMI.